Advances in Immune Microenvironment and Immunotherapy of Isocitrate Dehydrogenase Mutated Glioma - Yan, Dongming; Li, Weicheng; Liu, Qibing; Yang, Kun (Frontiers in Immunology, 2022)
The tumor immune microenvironment and immunotherapy have become current important tumor research concerns. The unique immune microenvironment plays a crucial role in the malignant progression of isocitrate dehydrogenase (IDH) mutant gliomas. IDH mutations in glioma can inhibit tumor-associated immune system evasion of NK cell immune surveillance. Meanwhile, mutant IDH can inhibit classical and alternative complement pathways and directly inhibit T-cell responses by metabolizing isocitrate to D-2-Hydroxyglutaric acid (2-HG). IDH has shown clinically relevant efficacy as a potential target for immunotherapy. This article intends to summarize the research progress in the immunosuppressive microenvironment and immunotherapy of IDH-mutant glioma in recent years in an attempt to provide new ideas for the study of occurrence, progression, and treatment of IDH-mutant glioma.